Propuesta de segmentación de los microempresarios para mejorar los programas de fomento de competitividad y productividad de la micro empresa en la provincia de Trujillo - Leyva Ramírez, Walter Santiago (2012)
The purpose of this research is to achieve promotion programs improve the competitiveness of micro entrepreneurs in the Province of Trujillo. Currently there are a number of programs for microenterprise development, but they are scattered and repetitively in different state institutions. For the present study used the deductive, inductive an analytical method; coming to the conclusion that through the segmentation is achieved such programs improve building on micro entrepreneurs, using research cluster analysis and factor analysis. Every Micro businessman has different needs and problems to be solved in terms of financial and business development services, in that sense it is understood that fostered entrepreneurship support activities according to your specifications and needs, according to a segmentation in their respective geographical area, can contribute to improving competitiveness.